Daily blood pressure variability in relation to neurological functional outcomes after acute ischemic stroke - Zhu, Yuan; Wu, Minghua; Wang, Huihui; Zheng, Yawei; Zhang, Siqi; Wang, Xintong; Wang, Shana; Fang, Zhuyuan (Frontiers in Neurology, 2023)
Background: Prior research has shown inconclusive findings regarding the relationship between blood pressure variability (BPV) in acute ischemic stroke (AIS) and functional outcomes. Most research has examined the connection between short-term BPV during the early 24–72 h after the occurrence of ischemic stroke and functional prognosis. We sought to determine the relationship between daily BPV at 7 days of commencement and functional outcomes during the 3 months following AIS. Methods: Altogether, 633 AIS patients admitted within 72 h of commencement were enrolled. AIS was defined as the time from the onset of symptoms to 7 days. Throughout this period, blood pressure (BP) was recorded twice daily (casual BP cuffs). The daily BPV, with standard deviation (SD) and coefficient of variation (CV), was calculated and matched to the functional results. The adverse outcome was characterized as mRS(modified Rankin scale)≥3, which comprised the recurrence of stroke, clinical intracranial bleeding, and death. Results: In total, 633 participants were included, and the incidence of adverse outcomes was 14.06% (89/633). There was a significant positive correlation between daily BPV and adverse outcomes but not between mean BP and risk. Smooth curve fitting revealed a U-shaped connection between the mean BP and adverse clinical outcomes. Multivariable logistic regression analysis showed an independent correlation between daily BPV and an adverse outcome in the top vs. bottom quartile of systolic BPV (odds ratio [OR] = 2.4, 95% confidence interval [CI]: 1.17–4.96, P = 0.018 for SD; OR = 2.4, 95% CI:1.17–4.93, P = 0.017 for CV) during a 3-month follow-up period. Identical results have been reported for the diastolic BPV. Conclusions: Irrespective of BP level, elevated daily systolic BPV and diastolic BPV in AIS were associated with an increased risk of adverse outcomes within 3 months. We also discovered a U-shaped association between the mean BP and adverse clinical outcomes. These findings suggested that BPV should be a risk factor of adverse outcome after ischemic stroke, which provided a new insight for BP management strategy.